Prevalence of multidrug-resistant tuberculosis at a regional drug-resistant tuberculosis center of Maharashtra - Gauri Suhas Kulkarni; Supriya Dhakne Palwe; Nilesh P Patil; Abhijit J Telkhade; Jui Kadukar (Indian Journal of Respiratory Care, 2020)
Introduction: Multidrug-resistant tuberculosis (MDR-TB) has created a significant health problem in most of the countries, and it is an obstacle to effective TB control. Aims and Objectives: The study aims to study the prevalence of MDR-TB among new cases, retreatment cases and to study the rate of MDR-TB detection among suspected cases of Category I (CAT I) failure, CAT II failure and at the start of CAT II. Patients and Methods: The present retrolective study was conducted by reviewing the records of diagnosed MDR-TB patients at a drug-resistant TB center from January 2012 to December 2013. The data of new and retreatment pulmonary TB (PTB) cases diagnosed during that period were collected. The data were analyzed to find out the prevalence of MDR-TB, and the rate of MDR-TB detected among each CAT. Results: The prevalence of MDR-TB in new cases was 0.10% and that of retreatment cases was 4.3%. The rate of MDR-TB detection among suspected cases of CAT I failure was 16.8%, 52.4% in CAT II failure, 11.6% at the start of CAT II, 11.7% among sputum positive during any month follow-up, 6.6% among MDR-TB contacts. Conclusion: Timely suspicion and diagnosis of MDR-TB and treatment are important in new and retreatment cases. All relapse or defaulter patients should be screened for MDR-TB at the start of CAT II treatment. MDR-TB should be suspected in any sputum-positive TB patient during treatment/sputum positive relapse/defaulter PTB.